Stages of BMI, Glucose Control, and Endothelial Cell Activation in Malignancy with Diabetes Patients - Widjaja, Sry Suryani; Syahputra, Muhammad; Ginting, Almaycano (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Abnormalities of glucose metabolism in diabetes can be an independent risk factor for the development and prognosis of cancer; it caused endothelial cell activation, inflammatory reactions. Hemostatic disorders, thrombosis, and various human organ damaged that will increase the morbidity and mortality rate. Diabetes was predicted to reach 552 million by 2030 in conjunction with rapid social and cultural changes. With the changes in lifestyle, body mass index (BMI) plays an important role in increasing the risk of metabolic diseases like diabetes type 2. One sign of endothelial cell activation is an increase in Von Willebrand Factor, which can be an early sign of increased coagulation activation until thrombosis occurs. AIM: The aim of the study was to determine the correlation between BMI, glucose control, and endothelial cell activation in malignancy with diabetes patients. METHODS: This is a case-control study with eighty samples. BMI, HbA1C, vWF, and D’dimer were measured. RESULTS: There is a statistical significant correlation between blood glucose and HbA1C (p = 0.00), blood glucose and BMI (p = 0.037), HbA1C an BMI (p = 0.029), HbA1C and vWF (p = 0.03), HbA1C and age (p = 0.009), D’Dimer and vWF (p = 0.00), and age and BMI (p = −0.019), but no statistical significant between vWF and BMI (p = 0.97), vWF and age (p = 0.36). CONCLUSIONS: There was an increased risk of thrombosis in malignancy with diabetes cases. BMI showed a significant correlation with blood glucose controlled, blood glucose control showed a significant correlation with the activation of the endothelial cell and hypercoagulable state.